The type Ia supernova SNLS-03D3bb from a super-Chandrasekhar-mass white dwarf star - Andrew Howell, D.; Sullivan, Mark; Nugent, Peter E.; Ellis, Richard S.; Conley, Alexander J.; Le Borgne, Damien; Carlberg, Raymond G.; Guy, Julien; Balam, David; Basa, Stephane; Fouchez, Dominique; Hook, Isobel M.; et al. (Nature, 2006)
Candle in the wind Type Ia supernovae are used as cosmological distance indicators. It is through them that the accelerating expansion of the Universe was detected, and with it the implied existence of dark energy. Their presumed reliability as 'standard candles' stems from the fact they have a fixed amount of fuel and a uniform trigger: they are predicted to explode when the mass of the white dwarf nears 1.4 solar masses, the 'Chandrasekhar' mass. Howell et al . now show that the high-redshift supernova SNLS-03D3bb does not play by these rules: its exceptionally high luminosity and low kinetic energy imply a super-Chandrasekhar mass progenitor. So future cosmological studies may need to consider possible contamination from such events when calculating distances. The high-redshift supernova SNLS-03D3bb has an exceptionally high luminosity and low kinetic energy, which both imply a super-Chandrasekhar mass progenitor. The accelerating expansion of the Universe, and the need for dark energy, were inferred from observations 1 , 2 of type Ia supernovae. There is a consensus that type Ia supernovae are thermonuclear explosions that destroy carbon–oxygen white dwarf stars that have accreted matter from a companion star 3 , although the nature of this companion remains uncertain. These supernovae are thought to be reliable distance indicators because they have a standard amount of fuel and a uniform trigger: they are predicted to explode when the mass of the white dwarf nears the Chandrasekhar mass 4 of 1.4 solar masses ( M ⊙ ). Here we show that the high-redshift supernova SNLS-03D3bb has an exceptionally high luminosity and low kinetic energy that both imply a super-Chandrasekhar-mass progenitor. Super-Chandrasekhar-mass supernovae should occur preferentially in a young stellar population, so this may provide an explanation for the observed trend that overluminous type Ia supernovae occur only in ‘young’ environments 5 , 6 . As this supernova does not obey the relations that allow type Ia supernovae to be calibrated as standard candles, and as no counterparts have been found at low redshift, future cosmology studies will have to consider possible contamination from such events.